Generating X-ray Images from Point Clouds Using Conditional Generative Adversarial Networks - Haiderbhai, Mustafa; Ledesma, Sergio; Navab, Nassir; Fallavollita, Pascal (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2020)
Simulating medical images such as X-rays is of key interest to reduce radiation in non-diagnostic visualization scenarios. Past state of the art methods utilize ray tracing, which is reliant on 3D models. To our knowledge, no approach exists for cases where point clouds from depth cameras and other sensors are the only input modality. We propose a method for estimating an X-ray image from a generic point cloud using a conditional generative adversarial network (CGAN). We train a CGAN pix2pix to translate point cloud images into X-ray images using a dataset created inside our custom synthetic data generator. Additionally, point clouds of multiple densities are examined to determine the effect of density on the image translation problem. The results from the CGAN show that this type of network can predict X-ray images from points clouds. Higher point cloud densities outperformed the two lowest point cloud densities. However, the networks trained with high-density point clouds did not exhibit a significant difference when compared with the networks trained with medium densities. We prove that CGANs can be applied to image translation problems in the medical domain and show the feasibility of using this approach when 3D models are not available. Further work includes overcoming the occlusion and quality limitations of the generic approach and applying CGANs to other medical image translation problems.
CRIS-Team Scopus Importer:2023-03-08